2015
DOI: 10.2527/jas.2014-8514
|View full text |Cite
|
Sign up to set email alerts
|

Net energy content of dry extruded-expelled soybean meal fed with or without enzyme supplementation to growing pigs as determined by indirect calorimetry1

Abstract: Two experiments were conducted to determine the NE content of dry extruded-expelled soybean (DESBM) and the effect of a multienzyme carbohydrase (MC) mixture on the NE content of DESBM and to determine the effect of diet design on NE values in growing pigs using indirect calorimetry (IC). In Exp. 1, 24 barrows (19.6 ± 0.51 kg BW) were allotted in a completely randomized design to 4 dietary treatments: a corn–soybean meal basal diet (Diet A), a diet containing Diet A and DESBM in an 80:20 ratio with a constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
6
10
0
Order By: Relevance
“…However, physical activity was not measured in this study. The value for FHP (787 kJ/kg BW 0.6 /d) is similar to our previous work (Zhang et al., ; Li, Li, et al., ; Li, Lv, et al., ; Lyu, Huang, et al., 2018; Lyu, Li, et al., 2018) and was not affected by dietary treatment, which is consistent with the results of Velayudhan, Heo, and Nyachoti () and Heo, Adewole, and Nyachoti ().…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, physical activity was not measured in this study. The value for FHP (787 kJ/kg BW 0.6 /d) is similar to our previous work (Zhang et al., ; Li, Li, et al., ; Li, Lv, et al., ; Lyu, Huang, et al., 2018; Lyu, Li, et al., 2018) and was not affected by dietary treatment, which is consistent with the results of Velayudhan, Heo, and Nyachoti () and Heo, Adewole, and Nyachoti ().…”
Section: Discussionsupporting
confidence: 91%
“…The ME:DE ratio in experimental diets was within the range of values previously reported (Huang et al., ; Li, Li, et al., ; Lyu, Huang, et al., 2018; Lyu, Li, et al., 2018; Velayudhan et al., ). The NE:ME ratio in the diets was in agreement with data from Kim and Nyachoti () but was greater than the value reported by Noblet et al.…”
Section: Discussionsupporting
confidence: 86%
“…A comparison between the fed and the fasted state will contribute to identify specific metabolic indicator of maintenance in pigs [ 6 ]. However, the duration of fasting has not been consistent in different studies [ 7 , 8 ]. A series of studies have demonstrated that fasting duration plays a role in blood biochemistry and transcriptional regulation of metabolic genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of information about the measured net energy (NE) content of these ingredients and the NE values of these ingredients that are available are based on prediction equations using digestible energy (DE), metabolizable energy (ME) or digestible nutrients contents [ 7 ]. Prediction equations are used to estimate the NE content in swine diets and their use is supported by the results of some recent studies [ 8 , 9 ], however, others have reported differences between values obtained with prediction equations and those determined using the indirect calorimetry (IC) method [ 10 , 11 ]. Therefore, there is a need to further evaluate the NE values of these ingredients using prediction equations and empirical measurements so as to guide their use in formulating swine diets.…”
Section: Introductionmentioning
confidence: 99%